A qualitative look at parents’ experience of their child’s dental general anaesthesia - M. S. AMIN, R. L. HARRISON, & P. WEINSTEIN (Paediatric Dentistry, 2006)
Caries relapse after treatment of early childhood caries (ECC) under general anaesthesia (GA) has been frequently reported.